The political role of date palm trees in the Jordan Valley: The transformation of Palestinian land and water tenure in agriculture made invisible by epistemic violence. (March 2020) - Trottier, Julie; Leblond, Nelly; Garb, Yaakov
In the West Bank, date palm trees have been sweeping over the Jordan Valley at an accelerating rate since the 2000s. The current scientific literature has depicted this transformation as sustainable development. This article proposes a method to harness social sciences in a meaningful manner within the interdisciplinary study of agricultural transformation. Focusing on appropriation rather than bundles of rights, within an exploration of water and land tenure, allows uncovering actors and mechanisms that remain undetected by the current scientific discourse. Date palms transform both land and water tenure. As seasonal labor replaces sharecroppers that lived on site, the livelihoods, housing security, and food security of those practicing family farming are compromised. Geospatial analysis allows a triangulation of the results produced by qualitative methods. Mapping and quantifying the spatial progression of Israeli and Palestinian date palm trees between 1999 and 2016 allows assessing the number of sharecroppers displaced by date palm trees during that period. This demonstrates a Valley Clearance is now occurring, akin to the Highland Clearances that took place in 18th century Scotland. The present transformation of agriculture in the Jordan Valley has clear social and political impacts. Donors, the Palestinian Authority, and Palestinian date palm agribusinesses refer to the Palestinian water law within the perspective of a two state solution. The Israeli Water Authority and Israeli settlers further a network of wastewater reuse which stands as the only reliable source of water for date palm cultivation in the foreseeable future and contributes to the development of a one state solution. Meanwhile, Palestinians practicing family farming rely on legal pluralism to secure their access to water.